The growth paradigm and the failures of the alternatives within the system: notes towards a dystopian Marxism (Alternautas, 2024)
We start with two main hypotheses: a) the tendency to overproduction and expanded reproduction is inevitable in a context of production based on competition and the search for profit; b) conflicts for resources and the tendential degradation of the quality of life are also inevitable and are only going to worsen as the expanded reproduction takes its toll on the environment and on the material conditions for the reproduction of capital. This paper explores some underlying phenomena to support these claims, such as the Jevons Paradox, the Tendency of the Rate of Profit to Fall, and the Energy Return on Investment. Finally, it discusses the failure of some of the alternatives to the Growth Paradigm: Sustainable Development, Green Growth, Circular Economy and Degrowth.